Natural occurrence of entomophthoroid fungi of aphid pests on Medicago sativa L. in Argentina = Ocurrencia natural de hongos entomophthorales de áfidos plaga de Medicago sativa L. en Argentina - Manfrino, Romina Guadalupe; Zumoffen, Leticia; Salto, Cesar Eduardo; Lopez Lastra, Claudia Cristina (2018)
Four species of entomophthoroid fungi, Pandora neoaphidis (Entomophthorales: Entomophthoraceae), Zoophthora radicans (Entomophthorales: Entomophthoraceae), Entomophthora planchoniana (Entomophthorales: Entomophthoraceae) and Neozygites fresenii (Neozygitales: Neozygitaceae) were found to infect Aphis craccivora, Therioaphis trifolii, and Acyrthosiphon pisum and unidentified species of Acyrthosiphon on lucerne in Argentina. Samples were collected from five sites (Ceres, Rafaela, Sarmiento, Monte Vera and Bernardo de Irigoyen) in the province of Santa Fe. In this study, Zoophthora radicans was the most important pathogen and was recorded mainly on Acyrthosiphon sp. Zoophthora radicans was successfully isolated and maintained in pure cultures. This study is the first report of entomophthoroid fungi infecting lucerne (Medicago sativa L.) aphids in Argentina.